Sei sulla pagina 1di 29

Boolean Algebra (Binary Logic)

Theorem

A + 0 = A A + 1 = 1

Boolean Algebra (Binary Logic)

Theorem

A + 0 = A

A + 1 = 1

A + A = A

A + A’ = 1

Boolean Algebra (Binary Logic)

Theorem

A + 0 = A

A + 1 = 1

A + A = A

A + A’ = 1

A * 0 = 0 A * 1 = A

Boolean Algebra (Binary Logic)

Theorem

A + 0 = A

A + 1 = 1

A + A = A

A + A’ = 1

A * 0 = 0

A * 1 = A

A * A = A

A * A’ = 0

Boolean Algebra (Binary Logic)

Theorem

A + 0 = A

A + 1 = 1

A + A = A

A + A’ = 1

A + B = B + A

(A + B) + C = A + (B + C)

AB + AC = A(B + C)

A * 0 = 0

A * 1 = A

A * A = A

A * A’ = 0

A * B = B * A

(A * B) * C = A * (B * C)

(A + B)*(A + C) = A + BC

Boolean Algebra (Binary Logic)

AB + AC = A(B + C)

 A B C AB AC AB+AC B+C A(B+C) 000 0 0 1 010 011 100 101 1 1 0 111

Boolean Algebra (Binary Logic)

AB + AC = A(B + C)

 A B C AB AC AB+AC B+C A(B+C) 000 0 0 0 1 0 010 0 011 0 100 0 101 0 1 1 0 1 111 1

Boolean Algebra (Binary Logic)

AB + AC = A(B + C)

 A B C AB AC AB+AC B+C A(B+C) 000 0 0 0 0 1 0 0 010 0 0 011 0 0 100 0 0 101 0 1 1 1 0 1 0 111 1 1

Boolean Algebra (Binary Logic)

AB + AC = A(B + C)

 A B C AB AC AB+AC B+C A(B+C) 000 0 0 0 0 0 1 0 0 0 010 0 0 0 011 0 0 0 100 0 0 0 101 0 1 1 1 1 0 1 0 1 111 1 1 1

Boolean Algebra (Binary Logic)

AB + AC = A(B + C)

 A B C AB AC AB+AC B+C A(B+C) 000 0 0 0 0 0 0 0 1 0 0 0 1 0 010 0 0 0 1 0 011 0 0 0 1 0 100 0 0 0 0 0 101 0 1 1 1 1 1 1 0 1 0 1 1 1 111 1 1 1 1 1

Boolean Algebra (Binary Logic)

AB + AC = A(B + C)

A

B

A

C

AB + AC

Boolean Algebra (Binary Logic)

AB + AC = A(B + C)

A

B

A

C

AB + AC

A

B

C

A(B + C)

Boolean Algebra (Binary Logic)

AB + AC = A(B + C)

A

B

A

C

A

A

A

A

+ 0 = A + 1 = 1 + A = A + A’ = 1

AB + AC

A + B = B + A

(A + B) + C = A + (B + C) AB + AC = A(B + C)

A

B

C

A

A

A

A

* 0 = 0 * 1 = A * A = A * A’ = 0

A(B + C)

A * B = B * A

(A * B) * C = A * (B * C) (A + B)*(A + C) = A + BC

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = Z

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = Z

A’

B’

A’

B

A

B

Z

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = Z

A

A

A

A

+ 0 = A + 1 = 1 + A = A + A’ = 1

A + B = B + A

(A + B) + C = A + (B + C)

A * 0 = 0

A

A

A

* 1 = A * A = A * A’ = 0

A * B = B * A

(A * B) * C = A * (B * C)

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = Z A’( B’ + B) + AB = Z

A

A

A

A

+ 0 = A + 1 = 1 + A = A + A’ = 1

A + B = B + A

(A + B) + C = A + (B + C)

A * 0 = 0

A

A

A

* 1 = A * A = A * A’ = 0

A * B = B * A

(A * B) * C = A * (B * C)

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = Z A’( B’ + B) + AB = Z A’(1) + AB = Z

A

A

A

A

+ 0 = A + 1 = 1 + A = A + A’ = 1

A + B = B + A

(A + B) + C = A + (B + C)

A * 0 = 0

A

A

A

* 1 = A * A = A * A’ = 0

A * B = B * A

(A * B) * C = A * (B * C)

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = Z A’( B’ + B) + AB = Z A’(1) + AB = Z A’ + AB = Z

A

A

A

A

+ 0 = A + 1 = 1 + A = A + A’ = 1

A + B = B + A

(A + B) + C = A + (B + C)

A * 0 = 0

A

A

A

* 1 = A * A = A * A’ = 0

A * B = B * A

(A * B) * C = A * (B * C)

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = Z A’( B’ + B) + AB = Z A’(1) + AB = Z A’ + AB = Z

A

A

A

A

+ 0 = A + 1 = 1 + A = A + A’ = 1

A + B = B + A

(A + B) + C = A + (B + C)

A’B’ + A’B + AB = Z

A * 0 = 0

A

A

A

* 1 = A * A = A * A’ = 0

A * B = B * A

(A * B) * C = A * (B * C)

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = Z A’( B’ + B) + AB = Z A’(1) + AB = Z A’ + AB = Z

A

A

A

A

+ 0 = A + 1 = 1 + A = A + A’ = 1

A + B = B + A

(A + B) + C = A + (B + C)

A’B’ + A’B + AB = Z A’B’ + ( A’B + A’B) + AB = Z

A * 0 = 0

A

A

A

* 1 = A * A = A * A’ = 0

A * B = B * A

(A * B) * C = A * (B * C)

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = Z A’( B’ + B) + AB = Z A’(1) + AB = Z A’ + AB = Z

A

A

A

A

+ 0 = A + 1 = 1 + A = A + A’ = 1

A + B = B + A

(A + B) + C = A + (B + C)

A’B’ + A’B + AB = Z A’B’ + ( A’B + A’B) + AB = Z A’B’ + A’B + A’B + AB = Z

A * 0 = 0

A

A

A

* 1 = A * A = A * A’ = 0

A * B = B * A

(A * B) * C = A * (B * C)

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = Z A’( B’ + B) + AB = Z A’(1) + AB = Z A’ + AB = Z

A

A

A

A

+ 0 = A + 1 = 1 + A = A + A’ = 1

A + B = B + A

(A + B) + C = A + (B + C)

A’B’ + A’B + AB = Z A’B’ + ( A’B + A’B) + AB = Z A’B’ + A’B + A’B + AB = Z (A’B’ + A’B) + (A’B + AB) = Z

A * 0 = 0

A

A

A

* 1 = A * A = A * A’ = 0

A * B = B * A

(A * B) * C = A * (B * C)

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = Z A’( B’ + B) + AB = Z A’(1) + AB = Z A’ + AB = Z

A

A

A

A

+ 0 = A + 1 = 1 + A = A + A’ = 1

A + B = B + A

(A + B) + C = A + (B + C)

A’B’ + A’B + AB = Z A’B’ + ( A’B + A’B) + AB = Z A’B’ + A’B + A’B + AB = Z (A’B’ + A’B) + (A’B + AB) = Z A’(B’ + B) + (A’ + A)B = Z

A * 0 = 0

A

A

A

* 1 = A * A = A * A’ = 0

A * B = B * A

(A * B) * C = A * (B * C)

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = Z A’( B’ + B) + AB = Z A’(1) + AB = Z A’ + AB = Z

A

A

A

A

+ 0 = A + 1 = 1 + A = A + A’ = 1

A + B = B + A

(A + B) + C = A + (B + C)

A’B’ + A’B + AB = Z A’B’ + ( A’B + A’B) + AB = Z A’B’ + A’B + A’B + AB = Z (A’B’ + A’B) + (A’B + AB) = Z A’(B’ + B) + (A’ + A)B = Z A’(1) + (1)B = Z

A * 0 = 0

A

A

A

* 1 = A * A = A * A’ = 0

A * B = B * A

(A * B) * C = A * (B * C)

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = Z A’( B’ + B) + AB = Z A’(1) + AB = Z A’ + AB = Z

A

A

A

A

+ 0 = A + 1 = 1 + A = A + A’ = 1

A + B = B + A

(A + B) + C = A + (B + C)

A’B’ + A’B + AB = Z A’B’ + ( A’B + A’B) + AB = Z A’B’ + A’B + A’B + AB = Z (A’B’ + A’B) + (A’B + AB) = Z A’(B’ + B) + (A’ + A)B = Z A’(1) + (1)B = Z A’ + B = Z

A * 0 = 0

A

A

A

* 1 = A * A = A * A’ = 0

A * B = B * A

(A * B) * C = A * (B * C)

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = A’ + B = Z

A

A

A

A

+ 0 = A + 1 = 1 + A = A + A’ = 1

A + B = B + A

(A + B) + C = A + (B + C)

A * 0 = 0

A

A

A

* 1 = A * A = A * A’ = 0

A * B = B * A

(A * B) * C = A * (B * C)

Boolean Algebra (Binary Logic)

A’B’ + A’B + AB = A’ + B = Z

A’

B’

A’

B

A

B

A

A

A

A

+ 0 = A + 1 = 1 + A = A + A’ = 1

Z

A + B = B + A

(A + B) + C = A + (B + C)

A’

B

A * 0 = 0

A

A

A

* 1 = A * A = A * A’ = 0

Z

A * B = B * A

(A * B) * C = A * (B * C)